1995
DOI: 10.1681/asn.v5122032
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular abnormalities in children with autosomal dominant polycystic kidney disease.

Abstract: It is known that adults with autosomal dominant polycystic kidney disease (ADPKD) have an increased incidence of cardiovascular abnormalities, including mitral valve prolapse. The cardiac manifestations of ADPKD in the pediatric population have not been well established. To determine the cardiac manifestations of children with ADPKD, echocardiography was performed in 154 children of 66 families in which one parent has ADPKD. Eighty-six affected children and 68 unaffected children were evaluated in a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(17 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Because clinical data support conservation of cilia structure and function in the kidney and heart valves (13,14), we initiated experiments to determine whether primary cilia contribute to valvulogenesis and whether they are involved in the etiology of MVP by first performing immunohistochemistry (IHC) on murine and human mitral valve leaflets. Primary cilia were infrequently observed on valve endocardium at all time points analyzed (Fig.…”
Section: Primary Cilia Are Spatially and Temporally Regulated During ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Because clinical data support conservation of cilia structure and function in the kidney and heart valves (13,14), we initiated experiments to determine whether primary cilia contribute to valvulogenesis and whether they are involved in the etiology of MVP by first performing immunohistochemistry (IHC) on murine and human mitral valve leaflets. Primary cilia were infrequently observed on valve endocardium at all time points analyzed (Fig.…”
Section: Primary Cilia Are Spatially and Temporally Regulated During ...mentioning
confidence: 99%
“…neurologic tissues (10)(11)(12). A classic example is the ciliopathy, autosomal dominant polycystic kidney disease (ADPKD), in which ~25% of patients have mitral valve prolapse (MVP), a 10-fold increase above background (13,14). Both MVP and ADPKD have a congenital etiology and are characterized by excessive deposition of proteoglycans, as well as disorganization and fragmentation of the collagen and elastin in the ECM (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of cerebral aneurysms is also negligible in children, with only rare case reports. A high incidence of mitral valve prolapse (12%) in an older study [ 29 ] could not be confirmed subsequently [ 8 ]. The incidence of inguinal hernias appears quite high with around 10% in only two studies reporting on this outcome [ 2 , 9 ], and was significantly higher in the group of children presenting with ADPKD VEO [ 9 ].…”
Section: Clinical Manifestation Of Adpkd In Childhoodmentioning
confidence: 99%
“…ADPKD has been associated with major cardiovascular abnormalities such as MVP [32], mitral and aortic regurgitation [33], as well as idiopathic dilated cardiomyopathy, hypertrophic cardiomyopathy, and ventricular non-compaction [5]. Prevalence of CHD has previously only been reported in children with ADPKD [22]. Cardiovascular abnormalities in patients with ADPKD were first described in 1984 in 62 patients with ADPKD; only one of them had a congenital coarctation of the aorta [34].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital heart disease (CHD) has been reported to be more prevalent in children with ADPKD compared to the normal population (3.5% vs. 0.8%) [22]. In this study, we aim to evaluate the association of CHD in a large cohort of adult patients with ADPKD.…”
Section: Introductionmentioning
confidence: 99%